Detection of infectious bronchitis-like virus isolated from psittacines at breeding facilities - Ganita Kurniasih Suryaman; Retno Damajanti Soejoedono; Okti Nadia Poetri; Agus Setiyono; EKOWATI HANDHARYANI (Society for Indonesian Biodiversity, 2021)
Abstract. Suryaman GK, Soejoedono RD, Poetri ON, Setiyono A, Handharyani E. 2021. Detection of infectious bronchitis-like virus isolated from psittacines at breeding facilities. Biodiversitas 22: 4261-4265. Captive breeding of parrots has been carried out in Indonesia to fulfill market demand for pets and support conservation efforts. However, there is limited information about Infectious Bronchitis Virus (IBV) in captive parrots. Therefore, this study examines IBV virus in psittacines and observes the pathological changes in inoculated chicken embryos. Cloacal swabs were obtained from 31 psittacine birds consisting of 15 sulfur-crested cockatoos (Cacatua sulphurea), 10 palm cockatoos (Probosciger aterrimus), two blue and yellow macaws (Ara ararauna), two green-winged macaws (Ara chloropterus), and two scarlet macaws (Ara macao). Swabs were also injected for 9 days to obtain specific pathogen-free (SPF) embryonated chicken eggs, and allantoic fluids were collected after 7 days. The residual cloacal swabs and allantoic fluid samples were tested for IBV by reverse transcription polymerase chain reaction (RT-PCR) targeting spike 1 glycoprotein (S1) and nucleoprotein (N) gene by primer set XCE2+/XCE2- and IBVN+/IBVN-, while the harvested inoculated embryos were examined for histopathological lesions by hematoxylin-eosin staining. Three and one allantoic fluid of C. sulphurea and P. aterrimus respectively were found positive for IBV by primer set IBVN+IBVN-. However, there was no significant difference in the inoculated embryo's gross anatomy, and the slight histopathological changes observed were not caused by the virus. Therefore, it is unclear whether the IB-like virus causes clinical disease manifestation in both Psittacine species or the chicken embryo. This is the first study carried out on IB-like viruses for both species.